Identification of a novel missense variant in the LMX1B gene associated with nail-patella syndrome in a Chinese family - Sun, Qian; Ren, Yaqiong; Cao, Yue; Zheng, Wen; Su, Guanghao; Wang, Xiaodong; Wang, Hongying (Frontiers in Genetics, 2025)
BackgroundNail-patella syndrome (NPS) is an autosomal dominant disorder caused by the variants of the LMX1B gene, affecting several systems, including musculoskeletal, renal, and ocular systems. Despite the well-established genetic basis, the complicated relationship between genotype and phenotype still remains unclear. This study aimed to identify the genetic cause of NPS in a Chinese family and elucidate its potential contribution to the disease’s phenotypic spectrum.MethodsClinical data and peripheral blood samples were collected from the affected family. Whole-exome sequencing (WES) was conducted to identify potential pathogenic variants, followed by Sanger sequencing to validate the candidate variant. Bioinformatic tools were employed to predict the 3D structure alterations and pathogenicity of the variant. Wild-type and mutant LMX1B overexpression plasmids were constructed to investigate the functional consequences of the variant. Western blotting and immunofluorescence were conducted to measure the expression and localization of the protein.ResultsThe proband presented with clinical manifestations, including nail malformation, patella dysplasia, restricted elbow movement, and pes planus. Both his mother and sister exhibited symptoms related to the skeletal system. WES identified a novel c.812G>C (p.R271T) variant in the affected family members. Bioinformatic analyses revealed structural modification in the protein and predicted functional impairment. Western blotting showed no significant difference in the expression level between wild-type and mutant protein. However, immunofluorescence demonstrated distinct changes in the subcellular localization of c.812G>C mutant.ConclusionNPS is a rare multisystem disorder with variable clinical presentations. In this family, the skeletal system was mainly involved with variations among different members. Our study identified a novel c.812G > c variant in the LMX1B gene, changing the nuclear localization of the protein.